Calibration and experiment of the contact parameters for the discrete meta-simulation of peanut pods during harvest in saline soils - Chang, Zengcun; Hou, Jialin; Zuo, Baiqiang; Yin, Shiyang; Li, Dongjie; Wang, Yuanhao; Ji, Pengcheng; Wang, Dongwei (International Journal of Agricultural and Biological Engineering, 2025)
In this study, a simulation model of peanut pod particles during harvest in saline soil was tested to calibrate contact parameters. Discrete meta-fill models of peanut pods were generated by a 3D meter and EDEM software. The range of values of contact parameters for peanut pods was measured by conducting collision and other tests using a homemade test rig. The parameters that affect the significance of the simulation process of stacking angle were screened by the Plackett-Burman experiment, the steepest ascent experiment, and the Box-Behnken experiment. An optimization test determined the optimal simulation model parameters: The peanut pods had a Poisson’s ratio of 0.386 and a shear modulus of 3.04 MPa. The coefficient of recovery for pods-pods collisions was 0.335, the coefficient of static friction was 0.854, and the coefficient of rolling friction was 0.346. The coefficient of recovery of collision between the pods-65Mn steel was 0.339, the coefficient of static friction was 0.589, and the coefficient of rolling friction was 0.159. The test results showed a relative error of 0.42% between the stacking angle bench and simulation tests. The results can provide data support for studying the discrete metamaterial characterization of peanut pods. Keywords: peanut pods, saline soil, discrete element, contact parameter, stacking angle, calibration and experiment DOI: 10.25165/j.ijabe.20251804.9692Citation: Chang Z C, Hou J L, Zuo B Q, Yin S Y, Li D J, Wang Y H, et al. Calibration and experiment of the contact parameters for the discrete meta-simulation of peanut pods during harvest in saline soils. Int J Agric & Biol Eng, 2025; 18(4): 53–62.